THE CORRELATION OF COOPERATIVE LEARNING STRATEGY IN TEACHING ENGLISH AT ISLAMIC EDUCATION PROGRAMME DHARMAWANGSA UNIVERSITY MEDAN - Yani Lubis (AXIOM : Jurnal Pendidikan dan Matematika, 2016)
The objectives of this study were to examine whether, 1) the studentsare able to master in English, and 2) is there correlation betweencooperative learning strategy in teaching English or not. The populationof this research is the second semester year student of IslamicEducation Programme of Dharmawangsa University Medan. In gettingthe data, the writer used test and interview, but in analyzing the data, heused the Product Moment Correlation formula. Then the value that isgotten that is 1.488. And the value is confirmed to distribution t table.Where the value of t distribution in N = 57 and real a = 0,05 is 1.671,because of the tcounted (1.488) is lower than distribution value of ttable(1.671), it can be told that there is no significant correlation between theImplementating Of Cooperative Learning Strategy in Teaching Englishat the second semester year student of Islamic Education Programme ofDharmawangsa University Medan.Based on the counted the students'score that there are no difficulties in studying english, because thestudents who had taken as sample in this research not only understandEnglish well, but also getting high score in English. Eventhough eachother has no correlation.